HUBUNGAN PAPARAN PORNOGRAFI MELALUI ELEKTRONIK TERHADAP PERILAKU SEKSUAL REMAJA - Dewi, Ari Pristiana; Yutifa, Hasli '; ', Misrawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract Adolescent in their growth and development are aggregate that is risky to health problem, including adolescent sexual behavior. The aim of this research had to know correlation about the porn from electronic media in adolescent sex behavior in Pekanbaru. This research used descriptive correlation with cross sectional approach. The technique of taking the sample used purposive sampling with 99 respondent as samples. The data was taken by using quisioner form. The result of this study showed there were significant relationship between porn frequency toward adolescent sexual behavior (p value: 0,000  < 0,05) and there is no significant relationship between quantity of porn material and electronic media toward adolescent sexual behavior (p value: 0,966; 0,057 > 0,05). It is recommended for Government and Information Communication Department to monitor pornography in electronic media, family can observed activity of adolescent, and the teachers can increased the positive activity for adolescent. Keywords: electronic media, porn, adolescent sexual behaviour